A rare case of pregnancy in a patient with Prune belly syndrome - Satomi Morita; Ryuhei Nagai; Kazutoshi Hayashi (Elsevier, 2022)
Prune belly syndrome (PBS) is a congenital syndrome with three main features: abdominal wall dysplasia, urinary tract abnormalities, and bilateral undescended testes. The majority of reported patients are boys, ith only a few reported girls. Moreover, only one case of PBS in pregnancy has been reported in the literature. In this report, we describe the management of pregnancy in a woman who had fetal hydrops and abdominal wall dysplasia after birth and was diagnosed with PBS. The patient had no abnormal urinary tract morphology; however, magnetic resonance imaging showed thinning of the rectus abdominis and oblique abdominal muscles. Due to the possibility of the prolongedecond stage of labor caused by the inability to obtain effective contraction spontaneous vaginal delivery, we chose to perform cesarean section. The patient went into labor at 35 weeks and 2 days and gave birth to a baby weighing 2370 g. We suggest that understanding the pathophysiology of abdominal wall dysplasia, such as in PBS, can lead to a safe pregnancy and delivery.